Pemberian Ganti Rugi Pembebasan Hak Atas Tanah Untuk Kepentingan Umum: Studi Kasus Pembangunan Jalur Layang Joglo - Nasya Nur Fadillah (Universitas Kuningan, 2025)
Land acquisition for public interest is a crucial instrument in national infrastructure development. This study examines the regulation and implementation of compensation in land acquisition based on the principle of public interest, using the construction of the Joglo Flyover in Banjarsari District, Surakarta City as a case study. This study uses a juridical-sociological approach and is analyzed using Lawrence M. Friedman's legal system theory, which encompasses three elements: legal structure, legal substance, and legal culture. The study shows that structurally and normatively, land acquisition has been regulated in detail through Law Number 2 of 2012, the Job Creation Law, and its derivative regulations. However, implementation in the field shows obstacles in the legal culture aspect, such as disagreements over compensation values ​​and a lack of public trust in the appraisal process. This reflects the need for synergy between formal legal and social approaches to ensure substantive justice. This study recommends strengthening deliberation mechanisms, taking compensation values ​​into account the socio-economic aspects of residents, and the importance of building a participatory legal culture to support a just and sustainable development process.